The Completion of Terrorism According to the Indonesian Positive Law - Sri Suatmiati; Febrina Hertika Rani (Universitas Muhammadiyah Sidoarjo, 2018)
In positive law, completion of terrorism in Indonesia solved through Penal Policy/Policies of criminal law by issuing and publishing various legal products, a Substitute Regulation of Law (Perpu) No. 1 of 2002 regarding the eradication of criminal acts of terrorism, reinforced into Law Act No. 15 of 2003 the Government is also issuing Substitute Regulation of Law (Perpu) No. 2 of 2002 regarding the enactment of the Substitute Regulation of Law (Perpu) No. 1 in 2002 reinforced into Law Act No.16 of 2003 and Law Act No. 9 of 2013 regarding the prevention and eradication of criminal acts of Terrorism Financing, until forming the anti terror units from both the indonesian army forces, police or non governmental institutions. Police (Densus 88) as the main actor of law enforcement and disruption network of terror along with the Attorney General and justice system.